The Associations Between CYP2D6 Metabolizer Status and Pharmacokinetics and Clinical Outcomes of Venlafaxine: A Systematic Review and Meta-Analysis - Lin, Xiao-Qian; Wang, Ping; Cai, Wen-Ke; Xu, Gui-Li; Yang, Mei; Zhou, Meng-Di; Sun, Mei; He, Fang; He, Gong-Hao (Pharmacopsychiatry, 2019)
Background The association between CYP2D6 metabolizer status and clinical outcomes of venlafaxine was extensively investigated previously, but no widely accepted conclusion has been reached so far. To obtain a more precise estimation of the association, a systematic review by meta-analysis was conducted in the present study.Methods The PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, Technology of Chongqing, and Wan Fang Database were searched for eligible studies up to August 2018.Results Fourteen related studies involving 1035 patients were finally included. Significant associations were found among 3 CYP2D6 phenotypes (NM, IM, and PM) and most pharmacokinetic parameters of venlafaxine. However, CYP2D6 phenotypes were not associated with Hamilton Depression Rating Scale response of venlafaxine. In addition, we also found no significant association between CYP2D6 phenotype and overall rate of adverse events.Conclusions CYP2D6 metabolizer status had significant influence on venlafaxine pharmacokinetics, but insufficient evidence demonstrated that CYP2D6 metabolizer status was associated with its therapeutic effects and overall rate of adverse events, which provided further evidence regarding the relationship between CYP2D6 metabolizer status and venlafaxine.
Keywords: CYP2D6; meta-analysis; phenotype; venlafaxine; polymorphism